Rede de cooperação interorganizacional no trade turístico dos lençóis maranhenses – Barreirinhas (MA) - Bastos, Gisele Mendonça Furtado (2013)
This study aimed to analyze the configuration of a network of interorganizational cooperation in Lençóis Maranhenses in its constitutive elements and dynamic operation, aiming to contribute to the understanding of the phenomenon in a secluded destination, the ecological foundations and development of local tourism trade. In Brazil, studies on interorganizational cooperation are still considered relatively new. We notice the existence of a significant number of researches done in order to draw a diagnosis on the subject taking into account the reality of the country. In the context of tourism, networks of interorganizational cooperation are established to provide and nurture a tourist destination. Thus, we have focused on the study of interorganizational cooperation on a local, that is, a community dedicated to tourism and isolated from major centers of tourist receptors, such as the city of Barreirinhas in Lençóis Maranhenses . The research has a qualitative nature and the aims, is analytic. As for the media, it is a field research in form of case studies. We interviewed 16 business leaders, as well as 4 representatives of public bodies. Data collection was conducted through semi-structured interviews between July 22 and August 1, 2012. The categories were divided into 4 groups to ensure the achievement of the proposed objectives: (1) strategic, (2) organization, (3) social, and (4) policy. In analyzing the results, we used content analysis and discourse, with the aid of Atlas Ti version 6. The results show that, when considering the strategic dimension, cooperation activities established are more focused on the operational level to the strategic, with the presence of coopetitive practices among companies. The organizational dimension shows that the council is still in the process of maturation with respect to the formation of networks of inter-organizational cooperation. The social dimension, inturn, shows that the relationships between the actors encourage the sharing of knowledge, information and experiences, but not equally. Finally, the political dimension shows that there is an adversarial relationship between government and business.